Tinjauan Perkembangan Kendaraan Listrik Dunia Hingga Sekarang - S Kumara, Nyoman (Transmisi, 2008)
Electric vehicle is the one of important solution to reduce pollution result from fuel vehicle gas emission. By means of electrical motor the electric vehicle have  the power that convert from electrical energy to mechanical energy to turn its wheels.Many fields in electrical engineering support the electric vehicle development including electrical motor technology, power converter, digital processor based control system, and also battery technology for saving the electric energy.  Now the limited fosil based energy, the demanding of environment friendly of electric vehicle, and also technology support could motivate almost of  the auto mobile producers to give the attention  in electrical vehicle. This paper will try to explain the historical development of electric vehicle until now with the various of electric vehicles that have been produced  for instance hybrid, plug-in hybrid, and null emission electric vehicle will be presented.Keywords: electric vehicle development, hybrid electric vehicle, plug-in hybrid electric vehicle, null emission  electric vehicle